Genome Editing Provides New Insights into Receptor-Controlled Signalling Pathways. (May 2018) - Milligan, Graeme; Inoue, Asuka
Abstract : Rapid developments in genome editing, based largely on CRISPR/Cas9 technologies, are offering unprecedented opportunities to eliminate the expression of single or multiple gene products in intact organisms and in model cell systems. Elimination of individual G protein-coupled receptors (GPCRs), both single and multiple G protein subunits, and arrestin adaptor proteins is providing new and sometimes unanticipated insights into molecular details of the regulation of cell signalling pathways and the behaviour of receptor ligands. Genome editing is certain to become a central component of therapeutic target validation, and will provide pharmacologists with new understanding of the complexities of action of novel and previously studied ligands, as well as of the transmission of signals from individual cell-surface receptors to intracellular signalling cascades. Highlights: Genome editing is revolutionising all aspects of cellular biology, including pharmacological studies, and especially the ability to define 'on-target' effects of pharmaceutical ligands. The ability to eliminate expression from single or multiple genes provides 'knockout' rather than 'knockdown' cell lines derived from widely used model cell systems, as well as the capacity to explore the specific functions of closely related proteins. Such approaches have provided new insights into the biological roles of several poorly characterised GPCRs. Elimination of the expression of entire subfamilies of G protein α subunits and of widely expressed arrestin proteins has provided new understanding of the roles of G protein-mediated versus arrestin-mediated signalling from GPCRs. Genome editing will be expanded rapidly to target other cell signalling pathway components.